(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article briefly explores the journeys of the main characters, Hashimjon from Khudoyberdi To’xtaboyev’s «Sariq devni minib» and Harry from J.K. Rowling’s «Harry Poter va afsonaviy tosh», into worlds of magic and adventure. It highlights the fantastical aspects of Harry’s world and the adventurous experiences of Hashimjon.